The Clinical Outcome of Transforaminal Lumbar Interbody Fusion and Laminectomy for Single-level Lumbar Canal Stenosis with Grade 1 and 2 Spondylolisthesis - Ashok Sharma; Tarachand Suthar; Mudit Mathur; Vishnu Mittal; Shiv Bhagwan Sharma; Gaurav Mehta (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Lower back pain is a common cause of disability that affects mobility and quality of life in both adult and elderly patients. Initial management of lower back pain includes anti-inflammatory drugs, analgesics, physiotherapy, and epidural steroid infiltration. Despite multiple attempts of conservative management, if a patient develops refractory radicular pain with or without neurologic deficit and claudication, surgery is indicated. The two main approaches to surgical intervention include decompression (laminectomy only) and decompression with fusion (transforaminal lumbar interbody fusion [TLIF]). Materials and Methods: The study was done under the Department of Orthopedics at SRG Hospital, Jhalawar (Rajasthan, India), between May 2019 and November 2022. In this randomized study, we compare the clinical outcome of TLIF and laminectomy for single-level lumbar canal stenosis with Grade 1 and 2 spondylolisthesis. Forty patients with single-level lumbar canal stenosis with Grade 1 and 2 spondylolisthesis were randomly divided into two equal groups. Patients in both the groups were followed up for 2 years. Results: In this study, we also noted estimated amount of blood loss, procedure time, time taken for ambulation, length of hospitalization, and demography. The Oswestry Disability Index scores improved significantly postoperatively. The modified MacNab criteria suggest the outcomes rated as excellent/good rate of 90% in TLIF and 85% in laminectomy. Conclusion: We evaluated that TLIF procedures are associated with slightly more significant improvement in clinical outcomes in all of the scoring systems that were applied; TLIF provides early ambulation but higher cost of treatment and longer hospital stay compared to laminectomy. Laminectomy procedures are associated with lesser economic burden, lesser hospital stays, lesser blood loss, and shorten surgical duration compared to TLIF.